Considering the Role of the Arts and Aesthetics Within Maker-Centered Learning. (2nd October 2017) - May, Sarah; Clapp, Edward P.
Abstract : Throughout the past decade, the maker movement has become a cultural force, and maker-centered learning has grown in popularity. At the same time, the arts have remained marginalized throughout the educational sphere and limited scholarship recognizes the connections between the maker movement and arts learning. To explore this connection, we conducted a thematic analysis of interviews with maker educators and thought leaders, and we found that these educators rarely used arts and aesthetics-related terminology when speaking about the benefits of maker-centered learning. However, when these terms were used, they fell into three categories: objects, thinking skills and processes, and environments. We suggest that establishing a language of aesthetics in maker-centered learning might help arts and maker educators see themselves reflected in one another's work. Further, making such an aesthetic connection might provide young people with a deeper understanding of the beauty to be found in the made world.